Analysis of muscle forces acting on fragments in pelvic fractures - Elabjer, Esmat (Array, 2009)
Abstract: CT was used in 50 adult pelvic fractures to determine the size and the position of relevant muscles with regard to bony elements in order to calculate muscle forces acting upon certain pelvic portions. Muscle length was measured to calculate muscle volume and physiological muscle cross-section. Among others, the size and direction of muscle forces were calculated for iliac, pubic and ischiadic fractures. The strongest muscle acting in iliac fractures is m. gluteus medius. The strongest upward pulling of iliac bone fragments is exerted by the erector muscles, while the major anterior, medial and downward pulling is performed by the iliopsoas muscle. In pubic bone fractures, eight muscles push bone fragments downward, the strongest among them being m. adductor magnus. Two muscles pull them upwards: m.rectus abdominis and m. obliquus externus. Nine muscles are responsible for downward displacement of bone fragments in ischiadic fractures, but the strongest is m. semitendinosus. Calculation of moments of muscle forces acting upon bone fragments using CT of pelvic fractures gives additional data for planning of optimal operative treatment that can guarantee stable fixation in individual patients